2009
DOI: 10.18597/rcog.315
|View full text |Cite
|
Sign up to set email alerts
|

Doppler de arterias uterinas en el primer trimestre del embarazo para la detección de los trastornos hipertensivos asociados con el embarazo: estudio de cohorte. Bogotá (Colombia) 2007-2008

Abstract: Objetivos: determinar la utilidad diagnóstica y el poder de detección del índice de pulsatilidad anormal de las arterias uterinas durante el primer trimestre del embarazo en relación con la aparición de preeclampsia en una población de bajo riesgo.Metodología: estudio de cohorte prospectivo, en el cual se midió el índice de pulsatilidad de las arterias uterinas en 444 pacientes que asistieron a control prenatal normal entre las semanas 11 y 14 de gestación. Se evaluó de manera prospectiva la aparición de preec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…15 In addition, the Colombian guidelines showed that uterine artery Doppler had predicted a higher number of FGR when uterine artery pulsatility index with diastolic notching was found, or when the pulsatility index was increased, with a sensitivity and specificity of 67% and 45%, respectively, in the second trimester for severe FGR. It was described to be a better predictor for preeclampsia than FGR 15,30,31 as it is observed in this study (Table 2).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…15 In addition, the Colombian guidelines showed that uterine artery Doppler had predicted a higher number of FGR when uterine artery pulsatility index with diastolic notching was found, or when the pulsatility index was increased, with a sensitivity and specificity of 67% and 45%, respectively, in the second trimester for severe FGR. It was described to be a better predictor for preeclampsia than FGR 15,30,31 as it is observed in this study (Table 2).…”
Section: Discussionsupporting
confidence: 64%
“…20 Cortes-Yepes described that the uterine artery pulsatility index was higher in patients who will develop preeclampsia with a reference value of 95th percentile, supporting the idea that Doppler is a good predictor that should be included in routine examinations. 30 In this study, screening significantly increased the sensitivity and specificity by including uterine artery Doppler from 45.4% to 70.3% and from 73% to 93.8%, respectively. Additionally, it is important to highlight that the uterine artery Doppler is a noninvasive method without risk for the maternal-fetal binomial for the study of the uteroplacental circulation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Los resultados del mismo contribuirán al discernimiento de las distintas causas que pueden generan malformaciones fetales en mujeres embarazadas y plantear correctivos, con los consecuentes beneficios para las comunidades y para la Seguridad Social del Estado ecuatoriano. 6 El objetivo de la presente investigacion es determinar el tipo de malformaciones fetales cromosómicas o no, encontradas en la ciudad de Guayaquil-Ecuador y la edad en las que se presentan en la mujer ecuatoriana.…”
Section: Introductionunclassified